Collaborative Governance in Supervizing the Development of Seaweed Cultivation in Nunukan Kaltara Province Through Supervisor Community Group - Suhadi, ‎; Ahmad, Badu; Ibrahim, Akmal (KnE Social Sciences, 2025)
Based on the Decree of the Regent of Nunukan No. 188.45/486/X/2021 concerning the Determination of Superior Products, Mainstay Products and Potential Products for 2001-2026, seaweed is one of the renewable old resource commodities in the form of regional superior goods or services and will be developed collaboratively to create value chains so as to generate added value, increase community income and create jobs as well as become regional icons. In this study, the method used is the qualitative method which, according to Ansell, uses a qualitative descriptive approach. Five main indicators, namely face-to-face dialogue, trust building, commitment to the process, shared understanding and intermediate outcome uses data collection techniques through in-depth interviews with stakeholders, participatory observation in collaboration forums and policy documentation studies, meeting minutes, and other supporting documents. The purpose of this study is to identify and analyze the collaborative process between Pokmaswas, Regional Government, and other stakeholders in the supervision of seaweed cultivation, especially in the context of the effectiveness of zoning supervision and shipping flows and others. Expected results identification of effective collaboration models between Pokmaswas, Regional Governments/Prop Governments, and other stakeholders in supervision, to strengthen synergy and communication between parties, policy recommendations and supervisory strategies. . So that the impact of seaweed cultivation, like zone overlapping, and plastic waste can be minimized. In general, it can be concluded that with a collaborative government in optimizing Pokmaswas, seaweed cultivation in Nunukan can be sustainable.